2018
DOI: 10.3390/met8100747
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Partitioning, Carbide Precipitation, and Grain Size on Brittle Fracture of Ultra-High-Strength, Low-Carbon Steel after Welding by a Quenching and Partitioning Process

Abstract: To improve the weld zone properties of Advanced High Strength Steel (AHSS), quenching and partitioning (Q&P) has been used immediately after laser welding of a low-carbon steel. However, the mechanical properties can be affected for several reasons: (i) The carbon content and amount of retained austenite, bainite, and fresh martensite; (ii) Precipitate size and distribution; (iii) Grain size. In this work, carbon movements during the partitioning stage and prediction of Ti (C, N), and MoC precipitation at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Forouzan et al [44] studied the brittle fracture behavior of ultra-high-strength, lowcarbon steel welds after a quenching and partitioning (Q&P) process. This study performed laser welding on 'DOMEX 960' steel.…”
Section: Weldability Challenges Due To Steel Processing Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forouzan et al [44] studied the brittle fracture behavior of ultra-high-strength, lowcarbon steel welds after a quenching and partitioning (Q&P) process. This study performed laser welding on 'DOMEX 960' steel.…”
Section: Weldability Challenges Due To Steel Processing Conditionsmentioning
confidence: 99%
“…As shown in Figure 4, many particles, such as nitrides and carbides, can be seen in the HAZ. The authors observed Ti (C, N) particles nucleated and coarsened in the HAZ and the growth of nucleated carbides at the grain boundary [44]. In this regard, the welded joints of HSS and AHSS generally have lower m properties than the parent materials because the heat generated during welding the original microstructures in the FZ and the HAZ significantly.…”
Section: Weldability Challenges Due To Steel Processing Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The histograms of dimple size distribution for samples tested at different strain rates are plotted in Fig. It should be noted that quasi-cleavage and brittle fracture were also reported for some Q&P processed steels [304]. The fracture surface of the Q&P steels is to great extent determined by the tempered condition of the martensitic matrix.…”
Section: Fracture Surfacementioning
confidence: 91%